Endovascular treatment of intracranial vertebral artery unruptured dissecting aneurysms: Comparison of flow diversion and stent-assisted coiling or stenting alone - Li, Li; Xu, Gang-Qin; Gao, Hui-Li; Gao, Bu-Lang; Zhang, Kun; Wang, Zi-Liang; Li, Tian-Xiao (Frontiers in Neurology, 2022)
Purpose To investigate the effect and safety of flow diverters in the treatment of unruptured dissecting intracranial aneurysms of the vertebral artery in comparison with stent-assisted coiling or stenting alone. Materials and methods Patients with unruptured dissecting intracranial aneurysms of the vertebral artery treated with the flow diverter, stent-assisted coiling, or stenting alone were retrospectively enrolled. The clinical data were analyzed and compared. Results Twenty-five patients were enrolled in the flow diversion group and 42 patients in the stenting group. Twenty-six flow diverters were deployed in the flow diversion group. Immediate angiography revealed contrast agent retention within the aneurysm cavity in all patients. In the stenting group, 48 stents were deployed, and immediate angiographic outcome showed O'Kelly-Marotta (OKM) grade D in 18 (42.9%) aneurysms, grade C in 16 (38.1%), and grade B in 8 (19.0%). Periprocedural ischemic complications of thrombosis occurred in two (4.8%) patients and were treated with thrombolysis. In the flow diversion group, 19 (76%) patients underwent angiographic follow-up 3–46 (median 24) months after the procedure, with the OKM grade D in 11 (57.9%) patients, C in two (10.5%), and B in six (31.6%). The aneurysm recurrence rate was zero, and all diverters remained patent. Asymptomatic instent stenosis occurred in two (10.5%) patients. In seven of the ten patients with mild or moderate parent artery stenosis before the procedure who experienced angiographic follow-up, the stenosis was improved in five (71.4%) patients. In the stenting group, angiographic follow-up was carried out in 33 (78.6%) patients 6–58 months (median 34) after the procedure, with OKM grade D in 22 (66.7%) patients, grade C in five (15.2%), grade B in three (9.1%), and aneurysm recurrence (grade B, with increased contrast agent into the aneurysm cavity) in three (9.1%). Five (16.7%) patients experienced asymptomatic instent stenosis, and six of the 12 patients (50%) with parent artery stenosis were improved. Conclusion Flow diverters with or without selective adjunctive coiling for the treatment of unruptured dissecting intracranial aneurysms of the vertebral artery may be safe and effective with good occlusion effects not inferior to those of stent-assisted coiling and stenting alone even though the long-term effect still warrants confirmation.